1999
DOI: 10.1021/jf9808426
|View full text |Cite
|
Sign up to set email alerts
|

PCR−RFLP Analysis of Mitochondrial DNA:  A Reliable Method for Species Identification

Abstract: A method for identification of game species has been developed on the basis of the amplification of a specific part of the mitochondrial genome (tRNA(Glu)/cytochrome b) using the polymerase chain reaction (PCR). To distinguish between several game species, the obtained 464-bp-long PCR products were cut with different restriction endonucleases (RE) resulting in species-specific restriction fragment length polymorphism (RFLP). Even closely related deer species could be distinguished by application of one or two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(112 citation statements)
references
References 30 publications
2
106
0
4
Order By: Relevance
“…Confirmation of the meat species was according to Wolf et al [10]. Design of primers was based on the bovine Pth gene (K01938) and a 12S rRNA gene [8,21].…”
Section: Methodsmentioning
confidence: 99%
“…Confirmation of the meat species was according to Wolf et al [10]. Design of primers was based on the bovine Pth gene (K01938) and a 12S rRNA gene [8,21].…”
Section: Methodsmentioning
confidence: 99%
“…PCR-RFLP analysis of a conserved fragment from the mitochondrial 12S rRNA has been applied to identify several closely related domestic animal and game species (Fajardo et al, 2006;Pfeiffer, Burger, & Brenig, 2004;Wolf, Rentsch, & Hubner, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, the possible individual mutations make the selection of endonucleases in conserved restriction sites difficult, and several enzymes are often needed to discriminate between phylogenetically related species and when several species have to be differentiated simultaneously (Wolf et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The restriction digestion pattern obtained from a combination of PCR amplification and restriction enzymes for RFLP analysis proved to be a suitable marker tool for the identification of these three species of cattle (Lenstra et al, 2001;AbdulMawjood and Bülte, 2002). Therefore, this study revealed the significant role that PCR-based techniques can play in species identification, and emphasizes the importance of choosing the right genes with suitable variation rates (Brown, 1983;Wolf et al, 1999). This method was successfully used to type both Malaysian wild and domestic cattle, and has previously been used in species identification of game and domestic meats (Prado et al, 2007;Fajardo et al, 2009;Wang et al, 2010;Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 79%